T̤abakat-i-Nasiri : A General History of the Muhammadan Dynasties of Asia, Including Hindustan; from A.H. 194 (810 A.D.) to A.H. 658 (1260 A.D.) and the Irruption of the Infidel Mughals into Islam (vol. 1) - Minhaj-Ud-Din Abu-Umar-I-Usman, Maulana; Translated by Raverty, H. G., Major (Lahore Amir Publications, 1977)
A General History of the Muhammadan Dynasties of Asia, Including Hindustan; from A.H. 194 (810 A.D.) to A.H. 658 (1260 A.D.) and the irruption of the infidel Mughals into Islam
Translated from Original Persian Manuscripts.
Keywords: Islamic Empire -- India -- Ghaznevids -- Ghurids -- Muslims -- Asia--Orient -- Islamic countries -- Seljuks